Food Insecurity and Nutritional Inadequacy in Children and Adolescents of Basic Education Schools of Cantagalo District in São Tomé and Príncipe, Central Africa - Ferreira, F. (2024)
Food insecurity (FI) is a critical socioeconomic and public health problem globally, particularly affecting children's nutritional status and development. This cross-sectional study aimed to assess the prevalence of nutritional inadequacy among children and adolescents in the Cantagalo district of S & atilde;o Tom & eacute; and Pr & iacute;ncipe (STP), in Central Africa. It also assessed their households' FI situation and examined sociodemographic, anthropometric, and nutritional characteristics associated with severe FI. Data included 546 children/adolescents (51.8% males, aged 9-15 years) from the eight public basic education schools. A structured questionnaire provided sociodemographic data, while anthropometric measurements assessed nutritional status. Dietary intake data were gathered using a single 24 h dietary recall, and the adjusted prevalences of nutritional inadequacy were obtained using version 2.0 of the PC-Software for Intake Distribution Estimation (PC-SIDE (R)). The Household Food Insecurity Access Scale was used to assess FI, and households were classified as severely or non-severely food insecure. Multivariable binary logistic regression models adjusted for potential confounders identified factors related to FI. Children's/adolescents' thinness was exhibited in 34.1% of participants, and over 95% had inadequate intake of essential micronutrients, including iron. Notably, 73.7% were severely food insecure. A higher severity of FI was positively associated with a lower intake of iron and certain household head characteristics, such as being female or older, and negatively associated with having a home garden.